Washeteria closures, infectious disease and community health in rural Alaska : a review of clinical data in Kivalina, Alaska - Thomas, Timothy K; Bell, Jake; Bruden, Dana; Hawley, Millie; Brubaker, Michael
Background Kivalina is a northwest Alaska barrier island village of 400 people vulnerable to storm surges exacerbated recently by delayed winter sea and shore ice formation The village has no in-home piped water or sewage; the “washeteria” is the only structure providing public showers, laundry facilities and flush toilets In October 2004, a storm damaged the washeteria septic system resulting in prolonged facility closures We assessed rates of gastrointestinal, respiratory and skin infections potentially impacted by prolonged washeteria closures Methods We obtained washeteria closure dates from 2003 to July 2009 and defined >7 day closure as prolonged We received de-identified data on all Kivalina clinic visits from 2003 to 2009 and selected visits with ICD-9 diagnosis codes for respiratory, skin, or gastrointestinal infection; subsequent same patient/same illness-category visits within 14 days were excluded We compared annual visit rates, for all ages combined, before (2003–2004) and after (2005–2009) the “2004” storm Results The washeteria had prolonged closures for 34 days (47%) in the 2 years 2003–2004 and 864 days (517%) between January 2005 and July 2009 Closures ranged from 8 to 248 days Respiratory infection rates declined significantly from 132 visits/person/year in the 2003–2004 period to 099 visits/person/year in the 2005–2009 period There was a significant increase in skin infection rates after 2004, peaking at 028 visits/person/year in 2007 and then declining significantly to 015 visits/person/year in 2009 Gastrointestinal infection rates remained stable and low throughout (average: 005 visits/person/year) No temporal association was observed between respiratory, gastrointestinal or skin infection rates and prolonged washeteria closures Conclusion The Kivalina washeteria was closed frequently and for extended periods between 2005 and 2009 Initial closures possibly resulted in increased skin infection rates No increase in respiratory or gastrointestinal infections was noted ...